Refugee Admissions and Public Safety: Are Refugee Settlement Areas More Prone to Crime?. Issue 1 (March 2021) - Amuedo-Dorantes, Catalina; Bansak, Cynthia; Pozo, Susan
According to the United Nations High Commissioner for Refugees, the number of refugees worldwide rose to 25.9 million in 2018. Despite the increased need for refugee resettlements, resistance to the welcoming of refugees appears to have grown. The perception that refugees may engage in criminal behavior has served as fuel for closing the door to refugees in the United States and Europe. Is there any basis for this fear? We exploit variation in the geographic and temporal distribution of refugee resettlements across counties to ascertain if their presence can be linked to greater local violence in the case of the United States. We fail to find any statistically significant evidence of refugee resettlements raising local arrest or offense rates. Institutions that help refugees assimilate into the US labor market may contribute to these favorable outcomes. Overall, these findings widen our understanding of refugee resettlement in the United States and suggest that the adoption of humanitarian efforts to support these international flows need not be discouraged.